Revitalizing American cities - Wachter, Susan M.; Zeuli, Kimberly (City in the twenty-first century book series., 2014)
Revitalizing American Cities explores the historical, regional, and political factors that have allowed some small industrial cities to regain their footing in a changing economy, and considers strategies cities can use for successful rebuilding.